Pengaruh Partisipasi Penyusunan Anggaran terhadap Motivasi Kerja Manajerial - Muammar Khadafi; Najiatul Husna; Nurul Safitri; Fera Fera; Tasya Afani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
For managers, budgeting is a very important issue that affects the future survival of the organization. Given that key stakeholders are often involved in budget preparation, this preparation process raises questions regarding the relationship between participation in budget preparation and management motivation and performance. This article explains that when subordinates are involved in management, they are more likely to accept budget goals and therefore more motivated to participate in budget planning. Another aspect is that participation in budget preparation has a positive impact on budget adequacy. If the budget is decided unilaterally, the opposite will be true. This involvement motivates subordinates to be more proactive in achieving budget goals. From another perspective, subordinate participation in budgeting means that planning results are more realistic because subordinates have more accurate information about local conditions than superiors.